Implikasi Hukum terhadap Penyalahgunaan Teknologi Deepkfake untuk Pemerasan (Sextortion) dalam Perspektif Hukum Teknologi Informasi di Indonesia - Wayan Zenitia Devi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The development of deepfake technology, which utilises artificial intelligence to manipulate images, videos and sounds, has led to a serious threat of sextortion. In the Indonesian context, high internet penetration and low awareness of digital security increase the risk of this crime. This research analyses the legal consequences of the misuse of deepfake technology in sextortion based on the Electronic Information and Transaction Law (UU ITE). Using normative juridical methods and descriptive-qualitative analysis, this research examines the legal challenges faced in enforcing sanctions against this crime and provides recommendations to strengthen the legal framework in Indonesia. The results show that there are gaps in the legal framework that need to be addressed, as well as the importance of education and capacity building of law enforcement in dealing with cybercrime. In addition, the development of more sophisticated deepfake detection technology is expected to be a solution in tackling this abuse in the future.